The The Relationship Between Perception of VIA Check-Up with the Interest Women of Reproductive Age Couples Conducting VIA Check-Up - Elok Diana Lorensa; Susanti Pratamaningtyas; Mika Mediawati; Indah Rahmaningtyas (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2023)
Cervical cancer commonly experienced by women in Indonesia, the second highest after breast cancer. Almost 70% of the patients are found at advanced stage. This is quite unfortunate because precancerous lesions can be early detected by VIA methods. The scope of VIA check-ups in the District of Kediri (0.3%) is still below the national target (≥80%). The factors likely prevent WCA from conducting VIA test are perceived barriers, lack of information about the test and fearness. The purpose of this study was to determine the relationship between perception of VIA checkups and women's interest in doing VIA checkups. The research design used was correlation analytic with cross sectional approach.. The population are 6,796 women aged 30-50 years, used accidental sampling with 99 women sample size, who met the inclusion criteria. The research instrument used questionnaire; the data were analyzed using the Spearman Rank correlation. The results showed that the majority of respondents had neutral perceptions (72.7%), moderate interest (77.7%), and neutral perceptions that had moderate interest (61.6%). Statistical tests is P-value 0,00. This study concludes that there was a correlation between perceptions of VIA checkups and women's interest in conducting VIA checkups. Continuous information is needed to build positive perceptions of cervical cancer to increase interest in VIA screening.